Effect of braking speed on the property of high-performance copper-based brake pads - WEI Dong-bin; ZHANG Lin; ZHANG Peng; WU Pei-fang; CAO Jing-wu; SHIJIA Cai-rang; DING Xiang-ying; ZHAO Shang-jie; QU Xuan-hui (Fenmo yejin jishu)
High-performance copper-based brake pads were prepared by the traditional powder metallurgy method, and the commercial copper-based brake pads were used as a comparison. The braking performance under the different braking speeds was studied on MM-1000Ⅱ friction and wear tester, and the surface morphology of the brake pads and the brake discs were analyzed. The results show that, with the increase of the braking speed, the friction coefficient of the self-made brake pads first decreases and then increases, while the friction coefficient of the commercial brake pads remains unchanged after decreasing. The reduction of friction coefficient is related to the formation of friction film. With the further increase of the braking speed, the rupture of the friction film results in the increase of the friction coefficient, while the softening of copper makes the friction coefficient decrease. The change of friction coefficient is subject to the combined action of the friction film and the copper softening. In the speed range of 180~350 km/h, the self-made copper-based brake pads have the higher friction coefficient and wear resistance than the commercial ones, and show the higher friction coefficient fluctuation in the process of the continuous emergency braking.